S-band gain and noise figure improvements in thulium-doped fiber amplifier by using macro-bending approach - Emami, Siamak Dawazdah; Abdul-Rashid, Hairul Azhar; Yasin, S.Z.M.; Shariff, K.A.M.; Mirnia, Seyed Edriss; Parvizi, Amin; Ahmad, Harith; Harun, Sulaiman Wadi (Springer, 2012)
A new method for gain and noise figure enhancements in S-band thulium-doped fiber amplifier (TDFA) co-doped with aluminum is demonstrated using a macro-bending approach. The macro-bending suppresses both the amplified spontaneous emission (ASE) at 800 and 1,800 nm wavelength region and consequently improves the S-band gain of the TDFA. Gain enhancements between 5 and 8 dB are obtained with the macro-bending between 1,420 and 1,480 nm. The macro-bending also reduces the noise figure of the S-band TDFA.